Levels of cytokines profile in polycystic ovary syndrome - Shafaq H. Hussein Al-Musawy; Ihsan E Al-Saimary; Maysoon Sherif Flaifil (Medical Journal of Babylon, 2018)
Background: Polycystic ovary syndrome (PCOS) is one of the commonest endocrine disorder of female at reproductive age and it's prevalence in general population as 20%–33%. Objective: The aim of this study was to measure the level of interleukin (IL) 18, IL 6, and tumor necrosis factor (TNF) in polycystic ovary women and compare their levels with apparently healthy control group. Materials and Methods: case-control study was carried out in Basra. In this study, blood samples from 73 women with PCOS and 73 healthy control women were collected from outpatients and private gynecological clinics and primary health care centers from different area of Basra during August 2016–March 2017 for estimation of their serum levels of IL6, IL18, and TNF alpha by using enzyme-linked immunosorbent assay technique. Results: It is found that serum levels of IL6, IL18, and TNF alpha were elevated in PCOS women, and we conclude that serum levels of IL6, IL18, and TNF alpha are highly statistically significance in PCOS women than in healthy control group. Conclusion: Levels of IL6, IL18, and TNF alpha were highly statistically significant in PCOS comparing to normal women, and these high levels were related to PCOS independent on the presence of obesity or hyperandrogenism.